2-[18F]fluoro-2-deoxy-d-galactose positron emission tomography guided functional treatment planning of stereotactic body radiotherapy of liver tumours. (January 2017) - Fode, Mette Marie; Petersen, Jørgen Baltzer; Sørensen, Michael; Holt, Marianne Ingerslev; Keiding, Susanne; Høyer, Morten
Abstract: Background and purpose: The aim of this study was to test the feasibility of functional treatment planning (FTP) using 2-[ 18 F]fluoro-2-deoxy-d -galactose positron emission tomography (FDGal PET/CT) in stereotactic body radiotherapy (SBRT) of liver tumours. Material and methods: Six patients with liver metastases from colorectal cancer (mCRC) and one patient with intrahepatic cholangiocarcinoma (IHC) were included. Two volumetric modulated arc therapy (VMAT) SBRT plans were created for each patient: a FTP in which sub-volumes of 10% (V′10%), 20% (V′20%) and 30% (V′30%) of the best functioning liver tissue derived from FDGal PET/CT were included in the optimisation, and an anatomical treatment plan (ATP) in which only anatomical structures were used for optimisation. Results: With FTP, the mean dose (Dmean ) to V′10%, V′20% and V′30% of the best functioning liver tissue was reduced by 15% (range:6–33%), 12% (range:8–27%) and 9% (range:6–20%) compared to ATP. V′10%, V′20% and V′30% of the best functioning liver tissue receiving less than 15 Gy (VD<15Gy ) was reduced by 6% (range:0–21%), 4% (range:0–10%) and 3% (range:0–7%) compared to ATP. Conclusion: FDGal PET/CT-guided SBRT of liver tumours is feasible and allows for sparing sub-volumes of the best functioning liver tissue while delivering a highly conformal radiation dose to the tumour.